Evaluating the Efficacy of Open Learning Platforms in Higher Education - Mufron, Ali; Mendes, Clara; Costa, Tiago (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rise of open learning platforms has transformed higher education by providing accessible, flexible, and cost-effective learning opportunities for diverse student populations. Traditional educational models often face challenges in accommodating students with varying learning preferences, geographical limitations, and financial constraints. Open learning platforms offer self-paced learning, interactive content, and collaborative tools that enhance student engagement and academic performance. This study aims to evaluate the efficacy of open learning platforms in higher education by examining their impact on student learning outcomes, engagement levels, and knowledge retention. A mixed-methods research design was employed, integrating quantitative analysis of student performance metrics with qualitative feedback from learner surveys and instructor interviews. Findings indicate that students using open learning platforms demonstrate improved academic performance, increased motivation, and enhanced critical thinking skills. Statistical analysis reveals a strong correlation between interactive learning features and student engagement. The study concludes that open learning platforms are effective tools for higher education, promoting inclusivity and personalized learning experiences. Future research should explore the long-term impact of open education on professional development and strategies for optimizing platform design to maximize learning effectiveness.